TPQ Teacher's Motivation in Teaching the Qur'an Viewed from the Perspective of Maslow's Theory of Needs - Indrioko, Erwin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to explore and describe in depth the motivation of TPQ teachers in teaching the Qur'an which is associated with the theory of needs developed by Maslow at TPQ Miftahul Jannah Kalangan Ngunut Tulungagung. This study uses a qualitative approach and this type of research is a case study. This study’s data sources were the head of the TPQ, students, and teachers. This study uses several methods in collecting data, namely: the participatory observation method, in-depth interview method, and documentation method. The results of the study stated that TPQ teachers thought that teaching the Qur'an was part of worship, teaching the Qur'an was following the orders of the Prophet Muhammad SAW, teaching the Qur'an was a practice that would never lose its reward, and teaching the Qur'an to children is part of the fun (entertainment). TPQ teachers in teaching the Qur'an are not based on the fulfillment of physiological needs, safety needs, social needs, esteem needs, and actualization needs but are based on the main intention, namely to worship Allah SWT.